Chondrolysis of the Hip following Septic Arthritis: A Rare Complication of Magnetic Resonance Arthrography - Haviv, Barak (Hindawi Publishing Corporation, 2013)
Magnetic resonance arthrography (MRA) is commonly used to detect labral tears of the hip. Complications of MRA are unusual and include minor reactions such as chemical synovitis and urticaria. This paper presents a rapidly progressive chondrolysis of the hip in a young patient after arthrography. The patient had suffered from acute septic arthritis and was treated by emergent arthroscopic surgery followed by appropriate antibiotics. At 18 months of followup, there were no signs of active infection but evidence of joint chondrolysis. Magnetic resonance arthrography (MRA) of the hip is an invasive procedure and should therefore be recommended judiciously. Post-MRA pain is common but often mild and temporary, while post-MRA joint infection is rare; nevertheless, severe joint pain and limitation should raise suspicion for septic hip.